A forecast study about the expected number tourists at city hotels in Dubai during expo year 2021 - A. Sathakathulla, A.; Ananthi, Ganesh (SPC Journal of Social Sciences, 2021)
Tourism has become the world’s third largest export industry after fuels and chemicals. The causality between inbound tourism and economic growth is bi-directional. These establishments like many others around the world and in the Emirates have seen a steep decline in the tourism department, in particular customer’s arrival and their number of days stay-in reputed hotels in Dubai. Obviously, it is due to the Pandemic and related worldwide travel restrictions. This business issue is taken into consideration, based on past data about a decade to improve customer’s expectations that makes economic development in Dubai tourism department. The forecast analysis is made by two key variables Tourists V/s nights they stay in. To arrive suitable forecast value, the analysis is done by three different methods based on extraneous variables in this current pandemic scenario.